2018
DOI: 10.1002/aoc.4330
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4/ZnMg(Al)O magnetic nanoparticles for efficient biodiesel production

Abstract: Fe 3 O 4 /ZnMg(Al)O solid base catalyst was prepared by calcining ZnMgAl-LDHs grown on the surface of magnetic Fe 3 O 4 synthesized by chemical coprecipitation. The magnetic property of the catalyst was studied by vibrating sample magnetometer. The results showed that the catalyst possessed excellent magnetic responsivity, and it could be recovered by external magnetic field. The magnetic catalyst was also characterized by ICP, TG-DTG, XRD, SEM, EDS, TEM and N 2 absorption-desorption. It was found that the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Excellent magnetic response resulting in high yield of 94% with a biodiesel conversion above 82% after seven cycles was detected using Fe 3 O 4 /ZnMg(Al)O magnetic nanoparticles in biodiesel production. 28 FESEM validated the aggregation and localization of nZVIs in F. diplosiphon. Elemental distribution provided a relative comparison of the nZVIs and the amount of iron detected (Figure 6), considering the fact that nZVIs aggregate differently based on varying nZVI-F. diplosiphon attachment.…”
Section: ■ Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Excellent magnetic response resulting in high yield of 94% with a biodiesel conversion above 82% after seven cycles was detected using Fe 3 O 4 /ZnMg(Al)O magnetic nanoparticles in biodiesel production. 28 FESEM validated the aggregation and localization of nZVIs in F. diplosiphon. Elemental distribution provided a relative comparison of the nZVIs and the amount of iron detected (Figure 6), considering the fact that nZVIs aggregate differently based on varying nZVI-F. diplosiphon attachment.…”
Section: ■ Discussionmentioning
confidence: 72%
“…It is known that nanoparticles improve catalytic efficiency during the transesterifcation process, resulting in high biodiesel production. Excellent magnetic response resulting in high yield of 94% with a biodiesel conversion above 82% after seven cycles was detected using Fe 3 O 4 /ZnMg­(Al)O magnetic nanoparticles in biodiesel production …”
Section: Discussionmentioning
confidence: 98%
“…Even more interesting results were obtained using Fe 3 O 4 /ZnMg(Al)O magnetic nanoparticles. Chen et al 51 . reported that lipase immobilized on Fe 3 O 4 /ZnMg(Al)O afforded a 94% biodiesel yield at a catalyst concentration of 3 wt%, 65 °C, 12:1 methanol / microalgal oil molar ratio, and 3 h of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles improve biodiesel synthesis displaying tremendous catalytic potentials for the transesterification of feedstock to biodiesel. 74,75 The utilization of nanoparticles during the transesterification phase has been proven to boost catalytic efficiency. 76 The impact of calcium oxide and magnesium oxide nano-catalysts on the synthesis of biodiesel using waste cooking oil was investigated by Tahvildari et al 77 A study was conducted by Baskar et al 78 to ascertain the best reaction conditions to obtain optimum biodiesel yield by employing zinc oxide nano-catalyst By adopting a central composite design embedded in response surface methodology tools, the authors were able to vary the reaction parameters (Alcohol: oil ratio, reaction temperature, time of reaction, and catalyst dosage).…”
Section: Nanoparticles and Their Usage In The Processing Of Biofuelmentioning
confidence: 99%